Comorbidity and outcomes among hospitalized patients with stroke: a nationwide inpatient analysis - Chen, Wei; Li, Dong (Frontiers in Neurology, 2023)
Objective We aimed to characterize healthcare utilization and comorbidity outcomes among hospitalized elderly stroke patients using a nationally representative dataset in the United States. Methods Using the 2019 National Inpatient Sample, patients aged 65 years or older with and without comorbidities who were hospitalized for acute stroke were identified using the International Classification of Diseases, Tenth Revision, Clinical Modification codes. Patient comorbidities were identified with the use of the Elixhauser Comorbidity Index. The prevalence of comorbidities, in-hospital mortality, length of stay, and total hospital costs were analyzed for these patients. Results Within 451,945 patients (mean age 78 years, 54.1% women, 73.7% white), we observed that more than 90% of patients had a minimum of two comorbidities. The median number of comorbidities was 4.0 (IQR 3.0–6.0). There was significant variation in the prevalence rate of comorbidities. The five most common comorbidities were uncomplicated hypertension (55.4%), paralysis (40.1%), congestive heart failure (39.8%), various neurological illnesses (38.3%), and complex hypertension (32.5%). After adjusting for patient- and hospital-level characteristics, a statistically significant association was observed between comorbidities and various adverse outcomes. Specifically, comorbidities were found to be significantly associated with an increased risk of inpatient mortality (odds ratio: 1.09; 95% CI: 1.08–1.11; P < 0.001), a longer duration of hospitalization (0.68 days; 95% CI: 0.66–0.71; P < 0.001), and higher total cost (1,874.9; 95% CI: 1,774.6–1,975.2; P < 0.001). Conclusion This national data suggests that comorbidity is common among hospitalized older stroke patients and substantially increases the healthcare burden and inpatient mortality in the United States. These findings underscore the integration of comorbidity management into the care of older stroke patients.